Dynamic Equivalence in Translation from English into Ibibio: An Experiment with the Nigerian National Pledge (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This research examined the translation procedures employed in achieving dynamic equivalence in translation from English language into Ibibio language using the Nigerian National Pledge as exemplifying text. The major aim was to see how the translators used some translation techniques to attain dynamic equivalence in their translations. The method of monolingual translation was applied with linguistic approach to translation theory as the theoretical base. The Nigerian National Pledge consisting of six sentences originally written in English was coded ST1 TO ST6 and the first translation carried out by a Professor of translation and a native speaker of the TL-Ibibio was coded TL1 to TL6. An alternate translation carried out by two linguists who are natives of the State but whose L1 is not the TL was coded AT1 to AT6. The two translations were analyzed simultaneously and areas of strengths and weaknesses were spotted. It was found out that the translatologist used more of literal method than the linguists while the linguists applied more of exegesis than literal method. The Professor/Translatologist used modulation in a few instances. The translations were similar in some portions of the text while there were a few divergences. The Translatologist performed better than the linguists in that he achieved dynamic equivalence in greater portion of the text than the linguists. Of the six sentences in the SL the Professor and the linguists failed to attain dynamic equivalence in one phrase. Overall, more than 80% dynamic equivalence was achieved in the translation. I therefore recommend that translators should work into the language of habitual use.